A new flavonoid glycoside from Tapinanthus sp. (Loranthaceae) and evaluation of anticancer activity of extract and some isolated compounds. Issue 16 (29th July 2022) - Gade, Isaac Silvère; Chadeneau, Corinne; Richard, Tagne Simo; Atchade, Alex De Théodore; Talla, Emmanuel; Seite, Paul; Vannier, Brigitte; Guillard, Jérôme; Laurent, Sophie; Henoumont, Celine; Nwabo, Armel H. Kamdje; Muller, Jean-Marc
Abstract: The present work describes the isolation and anticancer activity of Tapinanthus sp. which is a hemi parasitic plant harvested on Combretum glutinosum, the host plant. Phytochemical study afforded a new flavonoid glycoside, tapinantoside (1 ) isolated for the first time from natural source, alongside six known compounds (2 -7 ). Structure of compounds were elucidated by extensive spectroscopic analyses including 1 D and 2 D NMR, mass spectrometry and by comparison with literature data. The anticancer activity of extract and some isolated compounds were evaluated on glioblastoma (U87MG, C6) and prostate (PC-3) cancer cells. The methanol leaves extract showed good anticancer activity against U87 (IC50 = 21.40 µg/mL) and PC-3 cells (IC50 = 10.26 µg/mL). Compound 3 powerfully inhibits the proliferation of C6 (IC50 = 38.84 µM) and PC-3 cells (IC50 = 21.33 µM), while its effect was moderated on U87MG cells. Compound 1 and 7 were not active on all tested cancer cell lines. Graphical Abstract: UF0001